Pembangunan Karakter Anak Bangsa melalui Konsep Multikulturalisme - Nurcahyanti, Mei; Fitriana, Novita; Chan, Faizal; Noviyanti, Silvina (TSAQOFAH, 2024)
To build the character of the nation's future, a solution is needed, one of which is through education with the concept of multiculturalism. Multicultural education focuses on Indonesian human character which is carried out by forming thinking concepts, attitudes, actions and habits to shape conscience and character. Perceptions of Indonesian character are the basis for the characteristics of the Indonesian nation. Indonesia's strength is the energy that makes Indonesia a great country. A strong nation is created from the strong character of its people. Unsustainable national values instilled have the potential to become a source of division and conflict within a country. Therefore, multicultural education emphasizes the importance of paying attention to the interests of each culture and society in order to maintain and protect the nation's cultural and social identity. So that in the future Indonesia will have good morals and become an honorable country. This scientific article aims to describe multicultural education to build the personality of the nation's children. The method used is a literature review.